2019
DOI: 10.11113/amst.v23n2.147
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Composite Membrane for Palm Oil Wastewater Treatment

Abstract: Polyvinylidene fluoride (PVDF) composite membranes were prepared via phase inversion method by dispersing titanium dioxide (TiO2) in the dope solution. It is aimed to study the effects of TiO2 on the membrane surface properties and thus its separation performance. The PVDF membranes modified by various TiO2 contents were characterized with respect to cross-sectional structure, average pore size, effective porosity, hydrophilicity, permeability and rejection. Maximum values of membrane hydrophilicity, membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…The samples were then dried in an oven at 50 • C for 24 h. Samples were left for 10 min to cool down before taking their dried weight (w d ). The following equation was used to calculate the total porosity (ε) of each sample and then the average porosity for each membrane was determined [22]:…”
Section: Porosity and Pore Size Of Membranesmentioning
confidence: 99%
“…The samples were then dried in an oven at 50 • C for 24 h. Samples were left for 10 min to cool down before taking their dried weight (w d ). The following equation was used to calculate the total porosity (ε) of each sample and then the average porosity for each membrane was determined [22]:…”
Section: Porosity and Pore Size Of Membranesmentioning
confidence: 99%
“…The structure of the porous membrane and TiO 2 nanoparticle hydrophilicity were directly correlated with membrane porosity, which was responsible for the higher liquid uptake. Details of the membrane fabrication process and the property determination procedure can be found in a previous study [14]. The selected main properties of the used wastewater in this study have been analyzed as shown in Table 1.…”
Section: Preparation Of Ultrafiltration Systemmentioning
confidence: 99%
“…Percobaan filtrasi ini dilakukan dalam kondisi vakum yang dibuat menggunakan pompa peristaltik (Master flex model 7553-79, Cole Palmer) dengan permeat yang disedot dari ujung terbuka serat sebagaimana yang diilustrasikan pada Gambar 2 (Yuliwati, Porawati, and Elfidiah, and Melani 2019). Level cairan di tangki umpan dipertahankan konstan selama percobaan.…”
Section: Proses Ultrafiltrasiunclassified
“…Kualitas air permeasi dari air limbah berminyak yang diolah oleh membran yang dimodifikasi menunjukkan bahwa membran memiliki kinerja antifouling yang baik (Yuliwati, Porawati, and Elfidiah, and Melani 2019). Membran memiliki aplikasi yang luas dalam pengolahan air limbah tekstil dengan perolehan fluks yang lebih tinggi dan kontaminan yang lebih sedikit.…”
Section: Proses Ultrafiltrasiunclassified